Multilocal living and spatial development - Rainer Danielzyk; Andrea Dittrich-Wesbuer; Cédric Duchêne-Lacroix; Tatjana Fischer; Nicola Hilti; Manfred Perlik; Knut Petzold; Anne Ritzinger; Joachim Scheiner; Gabriele Sturm; Cornelia Tippel; Christine Weiske (Verlag der ARL - Akademie für Raumentwicklung in der Leibniz-Gemeinschaft, 2021)
This position paper was compiled by the members of the Working Group on "Multilocal living and spatial development" at the Academy for Territorial Development (ARL). In this position paper, the "Multilocal living and spatial development" Working Group at the Academy for Territorial Development (ARL) discusses a current social phenomenon that has spatial implications at various levels: multilocal living arrangements, i.e. the practice of living alternately at different locations. Increasing numbers of people live at more than one location and establish spaces for their everyday activities at each location (residential multilocality).
urn:nbn:de:0156-01231
Keywords: 710